The relative contributions of sagittal, frontal, and transverse joint works to self-paced incline and decline slope walking. (19th July 2019) - Yang, Zihan; Qu, Feng; Liu, Hui; Jiang, Liang; Cui, Chuyi; Rietdyk, Shirley
Abstract: Positive and negative work are generated at the lower limb joints in order to locomote over various terrains. Joint work quantifies the changes in energy that are necessary to adapt gait to environmental demands. The aim of this study was to quantify 3D joint work at the hip, knee, and ankle during slope walking. Work was calculated for ten males (23.9 ± 1.1 years) walking at a self-selected speed on inclines and declines (−20, −12, −6, 0, 6, 12, 20 degrees). Sagittal positive work significantly increased at the hip, knee, and ankle for incline walking (for example, hip positive work increased 153%, 280%, and 453% for 6, 12, and 20 degrees, respectively; knee and ankle positive work also increased) (p ≤ 0.05), in order to raise and propel the body forward. Sagittal negative work increased significantly at the hip, knee and ankle for decline walking (for example, knee negative work increased 193%, 355%, and 496% for −6, −12, and −20 degrees, respectively; hip and ankle negative work also increased) (p ≤ 0.05), in order to control body descent. These substantial changes in work will be especially challenging for people with compromised strength due to age and disease. Furthermore, changes in work were not limited to the sagittal plane: 46% of the total hip joint work occurred in the frontal and transverse planes for six degree decline walking. Thus, decline walking placed greater demands on the hip ab/adductors and rotators, and this may be related to the greater risk of falls observed for descent versus ascent.